Increasing the value and efficiency of herbicide resistance surveys. Issue 9 (15th March 2021) - Squires, Caleb C; Coleman, Guy RY; Broster, John C; Preston, Christopher; Boutsalis, Peter; Owen, Mechelle J; Jalaludin, Adam; Walsh, Michael J
Abstract: The scale of herbicide resistance within a cropping region can be estimated and monitored using surveys of weed populations. The current approach to herbicide resistance surveys is time‐consuming, logistically challenging and costly. Here we review past and current approaches used in herbicide resistance surveys with the aims of (i) defining effective survey methodologies, (ii) highlighting opportunities for improving efficiencies through the use of new technologies and (iii) identifying the value of repeated region‐wide herbicide resistance surveys. One of the most extensively surveyed areas of the world's cropping regions is the Australian grain production region, with >2900 fields randomly surveyed in each of three surveys conducted over the past 15 years. Consequently, recommended methodologies are based on what has been learned from the Australian experience. Traditional seedling‐based herbicide screening assays remain the most reliable and widely applicable method for characterizing resistance in weed populations. The use of satellite or aerial imagery to plan collections and image analysis to rapidly quantify screening results could complement traditional resistance assays by increasing survey efficiency and sampling accuracy. Global management of herbicide‐resistant weeds would benefit from repeated and standardized surveys that track herbicide resistance evolution within and across cropping regions. © 2021 Society of Chemical Industry. Abstract : A review of past and current approaches to herbicide resistance surveys, evaluating sample site selection, sampling and herbicide screening. Opportunities for improvements, including through adoption of technology, are presented.